Research on the Influence of Network Position on Corporate Social Responsibility: Moderating Effect Based on Ownership Concentration - Qu, Liang; Xu, Yuanjie; Guo, Yajing (Frontiers in Psychology, 2022)
Based on the social network theory and the institutional theory, this paper examines the influence of corporate network position on corporate social responsibility (CSR), and further explores the moderating role of ownership concentration Given the characteristics of CSR in different aspects, this paper explores the relationship between corporate economic CSR, environmental CSR and social CSR from the two aspects of the centrality and structural holes of interlocking directorate network based on the data of 1034 Chinese A-share listed companies from 2010 to 2019. The results show that the centrality and structural holes of interlocking directorate network have positive effects on the overall level of CSR, and the impacts on economic CSR and environmental CSR are stronger than that on social CSR. In addition, ownership concentration has a positive moderating effect on the relationship between corporate network position and CSR. These findings enrich the depth of research on CSR, clarify the influence of the characteristics of interlocking directorate network on CSR in different dimensions, and supplement the knowledgement of existing research.